Oxytocin during breastfeeding and maternal mood symptoms. (March 2020) - Whitley, Julia; Wouk, Kathryn; Bauer, Anna E.; Grewen, Karen; Gottfredson, Nisha C.; Meltzer-Brody, Samantha; Propper, Cathi; Mills-Koonce, Roger; Pearson, Brenda; Stuebe, Alison
Highlights: Breastfeeding is associated with higher mean oxytocin levels than bottle-feeding. Oxytocin may be lower during infant feeding in women taking antidepressants. We found no difference in oxytocin during breastfeeding by depression or anxiety status. Abstract: This study aimed to quantify the relationship between postpartum depression and anxiety, oxytocin, and breastfeeding. We conducted a longitudinal prospective study of mother-infant dyads from the third trimester of pregnancy to 12 months postpartum. A sample of 222 women were recruited to complete the Beck Depression Inventory II and Spielberger State-Trait Anxiety Inventory-state subscale, participate in observed infant feeding sessions at 2 and 6 months postpartum, and provide venous blood samples during feeding. Maternal venous oxytocin levels in EDTA-treated plasma and saliva were determined by enzyme immunoassay with extraction and a composite measure of area under the curve (AUC) was used to define oxytocin across a breastfeeding session. Linear regression was used to estimate associations between postpartum depression and anxiety as predictors and oxytocin AUC during breastfeeding as the outcome at both 2 and 6 months postpartum. Mixed models accounting for correlations between repeated oxytocin measures were used to quantify the association between current depression and/or anxiety symptoms and oxytocin profiles during breastfeeding. We found no significant differences in oxytocin AUC across a feed between depressed or anxious women and asymptomatic women at either 2 or 6 months postpartum. Repeated measures analyses demonstrated no differences in oxytocin trajectories during breastfeeding by symptom group but possible differences by antidepressant use. Our study suggests that external factors may influence the relationship between oxytocin, maternal mood symptoms, and infant feeding.